Functionality, Reliability, and Effectiveness of Information Technology Services in Supporting VAT Administration - Petrus Hery Setyo Nuryantoro; Irwan Sutirman Wahdiat; Aoliyah Firasati (Ali Institute or Research and Publication, 2025)
This study addresses the persistent challenges faced by taxable entrepreneurs (PKP) in utilizing information technology (IT) for Value-Added Tax (VAT) compliance, including data inconsistencies, reporting delays, and uneven system optimization. The research emphasizes the unique value of integrating IT functionality, infrastructure reliability, and overall effectiveness to improve VAT administration. Data were collected from PKP in the Cirebon 3 region through questionnaires (offline and online) and direct interviews. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to measure the level of IT utilization and its effect on VAT compliance. The f indings reveal that IT functionality, reliability, and effectiveness are at a high level, indicating that IT has been successfully implemented in VAT administration. Input and output tax administration scores were also categorized as high, and regression analysis demonstrated a positive and significant impact of IT on VAT compliance, both partially and simultaneously. These results highlight the critical role of the government’s integrated Coretax system and PKP’s capacity to adopt and optimize IT solutions. The study contributes by showing that combining functionality, reliability, and effectiveness creates a comprehensive framework that enhances compliance and reduces administrative friction in VAT management.